Pengaruh Penerapan Standar Akuntansi Pemerintahan Dan Kualitas Sumber Daya Manusiaterhadap Kualitas Laporan Keuangan Pemerintah Daerah Kota Kediri Periode 2017-2020 - Alisha Ristanti Hermawan (Program Studi Akuntansi IKOPIN, 2022)
Local Government Financial Reports (LKPD) are intended to fulfill the general purpose of financial reporting. Government Financial Reports depend on the quality of human resources and in the preparation of Local Government Financial Reports (LKPD) cannot be separated from Government Accounting Standards (SAP). This study was conducted to analyze the effect of partial or simultaneous application of Government Accounting Standards and human resources on the quality of the regional financial statements of the Kediri City Government for the 2017-2020 period. The population in this study were all employees of the Regional Revenue, Finance and Asset Management Agency, Kediri Sub-Accounting. . The sampling technique was saturated sampling technique and obtained a sample of 10 respondents. The analysis technique used is multiple linear regression analysis by considering the classical assumption test requirements which include normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. Hypothesis testing used t-statistics test to test the effect partially and F-statistics to test the effect simultaneously which was tested using SPSS v.23 for windows. The results of this study indicate that Government Accounting Standards and human resources partially or simultaneously affect the quality of the regional financial statements of the Kediri City Government for the 2017-2020 period.